BeingCare: a virtual communication window for wellbeing - Albuquerque, Carolina Marques (2021)
The powerful growth of technology granted users to take advantage of their resources in several areas such as health, education, politics, and others. However, human interaction continues poses several challenges, not only in isolation or care support scenarios, but also with human temporary constraints (inability to speak or move), even with the resource of technology. The BeingCare system - a proof-of-concept system based on Flutter – is a virtual window helping surpass communications constraints raised in wellbeing-related scenarios where direct interaction between the humans involved may be hindered. BeingCare was developed in Dart (backend) and Flutter (mobile and web front ends) and successfully deployed in iOS and Android with minor platform specific adaptions. Flutter enabled an easy integration of audio acquisition, processing, and classification. Edge computing approach for the audio classification was successfully addressed by using Tensorflow Lite, which grants local processing without the need of external services and any audio data exchange - enforcing the privacy and personal information data exchange in line with RGPD rules and mindset. Although not initially planned, the BeingCare back office was based entirely on the Dart language suggesting its adequacy to scopes beyond web/mobile using Flutter.